العادات المعوقة للزواج في ولاية كابيسا بأفغانستان : دراسة فقهية تقويمية - حامد، محمد فياض
This research is aimed to investigate on customs and traditions of marriage in Kapisa province, Afghanistan. It aimed at answering these main questions: customs and traditions that put obstacles to marriage; how to overcome these hurdles; and fix them within the Islamic paradigm in order to make it easy for everyone to marry and not make one to refuse marriage. The significance of this study is to try to figure out the solutions to the impediments of marriage in a particular Islamic society that suffers more than any parts of the country. Marriage has important role in the betterment of society and preserving human generation which is the main objective of Islamic law. Researcher uses inductive method for collecting data from Islamic sources of Al-Quran, hadith, past and contemporary Muslim jurists` opinions; and analytical method to analyze the information gathered from the mentioned sources including field study conducted through interview with religious scholars and societal reformists. Researcher reviewed customs and traditions at different stages of marriage such as traditions of marriage proposal, engagement period, marriage ceremony, and customs of wedding, and criticized those customs and traditions, and looked at those spheres which are mostly obstructive to the marriage process in Kapisa province. To end the research, some proposals for changing cultural practices hindering Islamic marriage among the eligible youths were made.